EVALUATING THE EFFECTIVENESS OF THE ALFACLASS PROGRAM IN VOCATIONAL EDUCATION: A CIPP MODEL APPROACH - Septi Diah Atiningtyas; Yeri Sutopo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Alfaclass program is an industry-based vocational education partnership designed to strengthen the alignment between vocational schools and the labor market by enhancing students' competencies and work readiness. However, the effectiveness of the program has not been comprehensively evaluated. This study aimed to evaluate the effectiveness of the Alfaclass program at SMKN 1 Lemahabang, Cirebon Regency, using the Context, Input, Process, Product (CIPP) evaluation model. A mixed-methods approach with a convergent parallel design was employed. Quantitative data were collected through questionnaires administered to teachers and students, while qualitative data were obtained through interviews, observations, and document analysis involving school leaders, productive teachers, students, alumni, and representatives of PT Sumber Alfaria Trijaya Tbk. The quantitative instrument was validated using Aiken's V and Percentage of Agreement, whereas qualitative data credibility was ensured through triangulation based on the trustworthiness criteria of Lincoln and Guba. Quantitative data were analyzed using descriptive statistics, T-score transformation, and the Glickman Quadrant Prototype, while qualitative data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the Context component was categorized as positive, whereas the Input, Process, and Product components were categorized as negative. The overall evaluation produced a (+−−−) pattern, indicating that the Alfaclass program was less effective. Although the program was relevant to industry needs and vocational education objectives, its effectiveness was constrained by limitations in resource readiness, implementation consistency, and graduate employability. The study concludes that improving institutional support, strengthening school–industry collaboration, enhancing learning facilities, and establishing a more transparent recruitment mechanism for Alfaclass graduates are essential to improve the effectiveness of industry-based vocational education programs.